Pengembangan Media Card Match Circle Pembelajaran Tematik Indahnya Keberagaman Di Negeriku Madrasah Ibtidaiyah Darul Huda Garum Blitar - Puji Asmaul Chusna (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2020)
Media is an important component in learning. The development of the Card Match Circle (CMC) media was developed based on the character of elementary school students who have high curiosity, love to play, the stage of thinking is still at a concrete stage, then a game is widely used as a variation of alternative learning to foster student motivation. By using the R&D method it is expected to be able to increase students' understanding, especially in daily life. Media variations that are tailored to the needs of students will be able to develop their skills in actively participating in using learning media to achieve maximum results. The results of the development of media experts, materials and student responses to the CMC media theme